2009
DOI: 10.1128/aac.00440-09
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Antidrug Antibodies on Plectasin Efficacy and Pharmacokinetics

Abstract: Plectasin is a 4.4-kDa antimicrobial peptide with the potential to be a treatment of infections caused by gram-positive bacteria. Since plectasin is a large molecule compared to conventional antibiotics, the development of antidrug antibodies (ADAs) could be anticipated. The immunogenic properties of plectasin were assessed through immunization studies. In mice treated for 5 days with one to two daily subcutaneous doses of plectasin, no antibody response was observed. If the animals were immunized again, after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…6,7,[9][10][11][12] AP138 is the product of an extensive lead optimization program based on a set of in silico generated plectasin variants. 13 In most cases, the single best antimicrobial agent should be selected for use because this minimizes side effects.…”
Section: Introductionmentioning
confidence: 99%
“…6,7,[9][10][11][12] AP138 is the product of an extensive lead optimization program based on a set of in silico generated plectasin variants. 13 In most cases, the single best antimicrobial agent should be selected for use because this minimizes side effects.…”
Section: Introductionmentioning
confidence: 99%
“…Intracellular persistence of bacteria that spread into the respiratory tract of CF patients may be one of the reasons responsible for the chronic nature of P. aeruginosa lung infections (17). It protects the bacteria from the host defense mechanisms and from the killing action of conventional antibiotics that hardly enter epithelial cells (28). Hence, the discovery of new antibiotics with new modes of action is highly demanding, and naturally occurring antimicrobial peptides (AMPs) represent potential alternatives (29,30).…”
mentioning
confidence: 99%
“…However, plectasin has a novel mode of antimicrobial action, specifically binding to the key bacterial cell wall precursor, lipid II (21), and thereby interfering with bacterial cell wall biosynthesis. NZ2114 is a new variant of plectasin with improved in vitro activity against staphylococci and streptococci, including those resistant to clinically available antibiotics (1,4,5,(19)(20)(21). Recent studies suggested that NZ2114 has potent activities both in vitro and in a number of animal models, including rabbit meningitis, murine peritonitis, and thigh infections and against various strains of Staphylococcus aureus and of Streptococcus pneumoniae (1,5,20).…”
mentioning
confidence: 99%